2014
DOI: 10.1093/jjco/hyu091
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Outcomes of Gastric Cancer Patients with Pulmonary Lymphangitis Carcinomatosa

Abstract: Pulmonary lymphangitis carcinomatosa caused by gastric cancer has some specific clinicopathological features. While the prognosis of gastric cancer patients with pulmonary lymphangitis carcinomatosa is extremely poor, some patients may have survival benefit from chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The role of lung metastasectomy in gastric cancer patients is still unclear (64). As many patients suffering from lung metastases form gastric cancers present synchronous carcinomatous lymphangitis or pleuritis, pulmonary metastasectomy has been rarely reported in this setting, thus only few data being available on short and long term outcomes (65,66).…”
Section: Gastric Cancersmentioning
confidence: 99%
“…The role of lung metastasectomy in gastric cancer patients is still unclear (64). As many patients suffering from lung metastases form gastric cancers present synchronous carcinomatous lymphangitis or pleuritis, pulmonary metastasectomy has been rarely reported in this setting, thus only few data being available on short and long term outcomes (65,66).…”
Section: Gastric Cancersmentioning
confidence: 99%
“…The reported median survival time of patients with pulmonary carcinomatous lymphangitis was 3 months, 23 and our study also confirmed similar prognostic outcomes. Effective chemotherapy was reported for carcinomatous lymphangitis, 24,25 but prompt chemotherapy was considered to be indemonstrable in patients with skeletal metastasis if the primary malignancy is not known. In this study, treatment for patients with respiratory failure was consequently only palliative treatment, which might not have improved their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnosis is currently based on the chest X-ray and High-Resolution Computed Tomography often confirmed by histopathological examination of biopsy-derived tissue [10]. In addition to symptomatic management standard treatment relies on chemotherapy [11], which is usually the only causative treatment 3 . It should also be noted that this type of patient is often in poor performance status with poor prognosis and choice of chemotherapy regimen might be challenging.…”
Section: Discussionmentioning
confidence: 99%